Physical Activity Across the Curriculum (PAAC): a randomized controlled trial to promote physical activity and diminish overweight and obesity in elementary school children - Donnelly, Joseph E. (2009)
OBJECTIVE: Physical Activity Across the Curriculum (PAAC) was a three-year cluster randomized controlled trial to promote physical activity and diminish increases in overweight and obesity in elementary school children. METHODS: Twenty-four elementary schools were cluster randomized to the PAAC intervention or served as control. All children in grades two and three were followed to grades four and five. PAAC promoted 90 minutes/wk of moderate to vigorous intensity physically active academic lessons delivered by classroom teachers. BMI was the primary outcome, daily PA and academic achievement were secondary outcomes. RESULTS: The three-year change in BMI for PAAC was 2.0 ± 1.9 and control 1.9 ± 1.9, respectively (NS). However, change in BMI from baseline to three years was significantly influenced by exposure to PAAC. Schools with ≥75 minutes of PAAC/wk showed significantly less increase in BMI at three years compared to schools that had <75 minutes of PAAC (1.8 ± 1.8 vs. 2.4 ± 2.0, p=0.02). PAAC schools had significantly greater changes in daily PA and academic achievement scores. CONCLUSIONS: The PAAC approach may promote daily PA and academic achievement in elementary school children. Additionally, 75 minutes of PAAC activities may attenuate increases in BMI.